Recovery from severe mental illness in Québec: The role of culture and place. (March 2019) - Boucher, Marie-Eve; Groleau, Danielle; Whitley, Rob
Abstract: This paper examines the role of culture and place in recovery from severe mental illness amongst a group of Québécois living in Montreal, Canada. Results indicate that dominant cultural characteristics of Québécois, such as a marked Roman Catholic heritage, use of the French language and a close affiliation with the natural territory of Québec can all play important roles in recovery from severe mental illness. The findings suggest that participants weave together places with cultural, familial and personal meaning to create their own healing landscapes. We propose ways to leverage place and dominant cultural traits to facilitate recovery. Highlights: Dominant cultural characteristics can play important roles in recovery from severe mental illness. Places with cultural, familial and personal meaning can be facilitators of recovery. Participants create their own healing landscapes. Possibility of leveraging place and dominant cultural traits to facilitate recovery.